P758 Use of a rapid syphilis test for syphilis diagnosis among patients presenting to an STI clinic in north carolina, USA. (14th July 2019) - Seña, Arlene; Mallette, Katie
Abstract : Background: Rapid treponemal antibody-based tests have been utilized for syphilis screening and diagnosis. In the United States (US), the Syphilis Health Check (SHC, Trinity Biotech) is the only FDA-cleared rapid test. However, there is a high proportion of false positives with SHC screening. We evaluated the performance of the SHC for syphilis diagnosis among patients presenting to an STI clinic in Durham, North Carolina (NC), US. Methods: Beginning in September 2017, the SHC was routinely performed for any patient in the STI clinic for whom a stat rapid plasma reagin (RPR) was requested and had no history of prior syphilis. The SHC and RPR were performed at the on-site laboratory using venous blood specimens. Confirmatory treponemal tests (e.g. enzyme immunoassay) were conducted for specimens with discrepant results at the state public health laboratory. We determined the performance of the SHC results in comparison with either a combined positive RPR/treponemal test or positive treponemal test as the standard for a "true positive." Results: Over a 16-month period, 182 unique patients who presented with symptoms and/or as contacts to syphilis underwent testing with a stat RPR and the SHC; the majority were African-American (83%) and male (74%). The SHC was positive in 66 patients; 9 of these cases had nonreactive RPRs but positive treponemal tests. The estimated sensitivity of the SHC was 91.3% (63/69), with a specificity of 97.3% (110/113). Of the 3 specimens with positive SHC but negative confirmatory testing, one was from an asymptomatic patient with contact to syphilis and an RPR 1:1. Conclusion: Rapid syphilis testing can be used to assist in the immediate diagnosis of STI clinic patients with suspected syphilis based on symptoms or exposure. The SHC had an acceptable sensitivity and specificity, with a low proportion of false-positives among a population with a high likelihood of syphilis infection. Disclosure: No significant relationships.